Investigating readiness of virtual classroom environment (VCE) among students / Wan Abdul Rahim Wan Mohd Isa, Vivi Noryati Ahmad and Dg Asnani Ag Nordin - Wan Mohd Isa, Wan Abdul Rahim; Ahmad, Vivi Noryati; Ag Nordin, Dg Asnani (Penerbit UiTM (UiTM Press), 2018)
Virtual classroom environment (VCE) is a platform for learners as it has the potential to increase learners’ academic performance. The main objective of this paper is to investigate the readiness for VCE among students at a local university in Malaysia. A survey was conducted with 217 respondents. Questionnaires administered comprised sections on the demography of respondents and their readiness for virtual classroom and Technology Readiness Index 2.0 (TRI 2.0). The Kruskal-Wallis test was conducted in the data analysis. The dimensions of the Technology Readiness Index; (i) insecurity, (ii) discomfort, (iii) innovativeness , and (iv) optimism, were analysed. The results showed only the ‘discomfort’ dimension had a statistically different average total score between the three generation groups according to their age, namely; (i) Generation X (those born between 1965 and 1979); (ii) Generation Y (born between 1980 and 1994); and (iii) Generation Z (born in 1995 or later). The mean rank of total score for ‘discomfort’ shows that Generation X has the highest mean rank among the three generation groups. Thus, the results suggest future qualitative studies to unravel the ‘discomfort’ dimension for Generation X group.